Effect of concurrent training, flexible nonlinear periodization, and maximal-effort cycling on strength and power - McNamara, J. M.; Stearne, D. J. (The Journal of Strength and Conditioning Research, 2013)
Although there is considerable research on concurrent training, none has integrated flexible nonlinear periodization and maximal-effort cycling in the same design. The purpose of this investigation was to test outcome measures of strength and power using a pretest-posttest randomized groups design. A strength and endurance (SE) group was compared with a strength, endurance, and maximal-effort cycling (SEC) group. Both groups used a flexible nonlinear periodization design. Thirteen male and 7 female students (mean ± SD: age, 22.5 ± 4.1 years; height, 173.5 ± 12.4 cm; weight, 79.4 ± 20.2 kg; strength training experience, 2.4 ± 2.2 years) participated in this study. Groups were not matched for age, height, weight, strength training experience, or sex, but were randomly assigned to an SE (n = 10) or SEC (n = 10) group. All training was completed within 45 minutes, twice per week (Monday and Wednesday), over 12 consecutive weeks. Both groups were assigned 6.75 total hours of aerobic conditioning, and 13.5 hours of free weight and machine exercises totaling 3,188 repetitions ranging from 5 to 20 repetition maximums. The SEC group performed 2 cycling intervals per workout ranging from 10 to 45 seconds. Pretest and posttest measures included chest press and standing broad jump. Analysis of variance showed that there were no significant differences between the SE and SEC groups on measures of chest press or standing broad jump performance (p, not significant). Paired sample t-tests (p = 0.05) showed significant improvement in strength and power in all groups (pretest to posttest), except for SE jump performance (p, not significant). In conclusion, adding maximal-effort cycling does not provide additional strength or power benefits to a concurrent flexible nonlinear training program. However, an exercise professional can take confidence that a concurrent flexible nonlinear training program can increase strength and power in healthy individuals.